Applying CBA to Decide the Best Excavation Method: Scenario During the Covid-19 Pandemic - Espinoza, Lisseth R. (2021)
On January 30 of 2020, The World Health Organization declared the pandemic crisis as the first public emergency with international importance. Because of this, many building projects were paralyzed since then and the building industry experienced changes that have brought the inclusion of new tools to achieve the objectives of the projects. The purpose of the present paper is to present the application of Choosing By Advantages (CBA) methodology to select the best alternative in the material removal system in the execution of basements in a project that was paralyzed by the health emergency COVID 19. CBA is a lean tool used to make decisions with clarity and transparency and in this case is used to consider the constraints of COVID-19 protocol to guide in decisions making. This methodology was applied to a case study for a building project in the basement construction phase that restarts its activities in the excavations. For that, an expert panel was formed to analyze and decide the best alternative solution. Finally, the selected alternative was implemented on-site, validating the methodology. It is concluded that CBA is an excellent tool to transparently document the selection process of the removal system. Additionally, this methodology allows including activities regarding the COVID-19 protocol, without affecting the project's productivity.